Who governs the High North? UNCLOS and Russia’s geopolitics in the Arctic - Zālīte, Ieva Estere (Riga Graduate School of Law, 2019)
The Arctic is under a threat of multiple levels. It is argued that the region is not only ungoverned properly by laws, it is also subjected to mass natural resource extraction, which is getting more approachable with years due to climate warming up. Countries surrounding the region are already competing for acquiring more of the Arctic space, some – more aggressively than the rest. This thesis will analyze the unmatched problems of the region, attempt to link them to prospective human rights violations, make doctrinal analysis of United Nations Convention on Law of the Sea in the context of the Arctic, review Russia’s agenda towards its Northern coast, and make an effort to sum up the presented arguments and problem analysis in order to provide a solution. The conclusion will stress that UNCLOS is not suited for the governance of the Arctic Ocean, and there should be a separated body of law for it that embodies the specifics of the region
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Environmental law; Arctic